Value-sensitive clinical accompaniment in community nursing science - Sonya Beukes; Anna G.W. Nolte; Ebin Arries (AOSIS, 2010)
Clinical community health facilities where undergraduate students are placed for their practical work in community nursing science are dynamic and have undergone major transformation over the past few years. In the clinical field, community nurses and undergraduate students are representative of the different races and language and ethnic groups in the South African population, with each group espousing different value systems. Both parties - students and community nurses - report that, due to these differences, value conflicts are experienced during clinical accompaniment and that this has negative effects on clinical learning in community nursing science. The goal of this study was to explore and describe the experiences of students with regard to value-sensitive clinical accompaniment in the community nursing environment. An exploratory, descriptive and contextual design was used. Interactions between community nurses and students during clinical accompaniment were explored for value sensitivity by means of video recordings,participant observation and focus group interviews. Data were collected by means of video recordings, participant observation and focus group interviews. The data were analysed and coded by the researcher and the external coder, using an inductive descriptive method to identify important segments of the regularity of behaviour. The focus group interviews were transcribed, analysed and coded by the researcher and the external coder, using Tesch's steps of analysis (Creswell 1994:155-156).Lincoln and Guba's criteria (1985:290) for trustworthiness were applied to the study. The general findings indicate that clinical accompaniment in community nursing is not value sensitive and, as a result, guidelines for value-sensitive clinical accompaniment need to be developed for undergraduate students in the community nursing environment. The following values (values for which guidelines need to be developed) were identified: respect during clinical accompaniment,value-sensitive communication and sensitivity to the quality of clinical accompaniment. Opsomming Kliniese gemeenskapsgesondheidsfasiliteite waar voorgraadse studente geplaas word vir gemeenskapsverpleegkundepraktika is dinamies en het groot veranderinge oor die laaste paar jare ondergaan. In die kliniese veld verteenwoordig gemeenskapsverpleegkundiges en voorgraadse studente verskillende rasse en taal- en etniese groepe in die Suid-Afrikaanse bevolking, elkeen met verskillende waardes. Albei partye - studente en gemeenskapsverpleegkundiges - het gerapporteer dat waardekonflik weens verskillende kulture en waardes tydens kliniese begeleiding ervaar word,wat kliniese leer op sy beurt in gemeenskapsverpleegkunde negatief beïnvloed. Die doel van die studie was om die belewenis van studente met betrekking tot waardesensitiewe kliniese begeleiding in gemeenskapsverpleegkunde te verken en te beskryf. 'n Verkennende, beskrywende en kontekstuele ontwerp is gebruik. Die interaksie wat tussen die gemeenskapsverpleegkundiges en studente tydens kliniese begeleiding plaasgevind het, is vir waardesensitiwiteit deur middel van video opnames, deelnemerobservasie en fokusgroeponderhoude verken. Die data wat deur middel van video-opnames en deelnemerobservasie ingesamel is, is deur die navorser en 'n eksterne kodeerder ontleed en gekodeer.'n Induktiewe beskrywende metode is gebruik om belangrike segmente van die gereeldheid van gedrag te identifiseer en beskryf. Fokusgroeponderhoude is deur die navorsers en 'n eksterne kodeerder getranskribeer, ontleed en gekodeer deur gebruik te maak van Tesch se stappe van analise (Creswell 1994:155-156). Lincoln en Guba (1985:290) se kriteria vir geloofwaardigheid is in die studie gebruik. Die algemene bevindinge dui daarop dat kliniese begeleiding in gemeenskapsverpleegkunde nie waarde-sensitief is nie. Gevolglik moet riglyne vir waarde-sensitiewe kliniese begeleiding vir voorgraadse studente in gemeenskapsverpleegkunde ontwikkel word. Die volgende waardes(waardes waarvoor riglyne ontwikkel moet word) is geïdentifiseer, naamlik respek tydens kliniese begeleiding, waarde-sensitiewe kommunikasie en sensitiwiteit vir gehalte van kliniese begeleiding.